Conventional pricing 2 - Coussins, Ricky (Henry Stewart Talks, 2010)
Price strategy, Strategic approach: understanding the situation regarding price drivers, Being strategic in relation to price, Price tactics, Discounting, Pricing and the PLC, Changing prices over time, Concluding thoughts, Further reading